Students' willingness to report weapons and violence in Cameroon secondary schools: Implications for students' well-being and school safety - Oben, Awu Isaac; Hui, Xu (Journal of Education, Health and Sport, 2025)
When weapons carrying and violence becomes a norm in schools, students stand at the crossroads of safety and risk. The decision to report weapons or violence in schools can prevent or perpetuate violence which disrupts education. This study investigated students' willingness to report violent acts or weapons brought to school. The survey research design was used. The population consisted of all students in the Fako Division, Southwest Region of Cameroon, with a sample of 581 students from Form Four, Form Five, Lower Sixth, and Upper Sixth of six targeted public secondary schools. Data collection were using questionnaires designed for secondary school students. The questionnaire's validity was confirmed through content-wise, construct-wise, and face-wise tests, and its reliability was confirmed through a pilot test on 20 students using the Cronbach Alpha test, indicating consistent responses, thereby confirming its reliability. The field data was processed using Epi-Data 3.0 and then exported to SPSS version 27 for consistency and validation checks. Quantitative data was analyzed using descriptive and inferential statistical tools, with hypotheses tested using t-tests and ANOVA tests for comparisons between groups like class, age, and socioeconomic status. Findings were presented at 95% confidence interval. The study identified several factors influencing students' willingness to report school violence or weapons on campus. Key differences emerged based on class, socioeconomic status, age, and knowledge of available resources, while gender showed no significant impact. Students with a positive perception of school climate and those educated in community or home values were likelier to report incidents. Reporting willingness also varied when the perpetrator was a friend, influenced by class, gender, or socioeconomic status.